KELEBIHAN ZAT BESI SEKUNDER BERKAITAN DENGAN SATURASI TRANSFERIN DAN FERITIN - Isabella Valentina; Ninik Sukartini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Iron overload disorder is a condition due to an excessive rate of iron acquisition compared to the rate of body iron loss that happens constantly. The clinical manifestations vary depending on the location of the damaged organs. Consequently, the symptoms of iron overload may mimic many diseases such as cirrhosis, diabetes mellitus, arthropathy, and skin pigmentation. The laboratory results which may point to iron overload are as follows: transferrin saturation >45%, serum ferritin level >300 ng/ml in men and >200 ng/ml in women. It is thus imperative that the molecular mechanism of iron metabolism and pathogenesis of iron overload are well understood in order to correct the interpretation of the laboratory results for iron overload. The standard management is blood removal by phlebotomy to maintain the level of the serum ferritin at 50 ng/mL in order to prevent irreversible hepatic cirrhosis